Analisis Gaya Bahasa Sarkasme Lagu “Suci Maksimal” oleh Musisi Jason Ranti - Andar Dittya Harsa; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
In Indonesia, there are many individual and group musicians who make music as a media for criticism of social or political aspects that are happening in the community. Like Iwan Fals, Slank, the Greenhouse Effect, Jason Ranti and others. This study aims to determine the meaning of the song